Factors That Influence Physical and Non-Physical Development in An Effort To Increase the Income of ST. Madyang Palopo Hospital - Puput Hasir; Muh Yusuf Q; Duriani Duriani (Jurnal Ekuilnomi, 2026)
Hospital physical development plays a crucial role in improving the quality of healthcare services and directly impacts revenue growth. Factors influencing physical development include infrastructure, technology, medical personnel, and facility management. Technological innovation and improvements in physical facilities contribute to service effectiveness, increased patient satisfaction, and increased patient interest. External factors such as government policies and demographic dynamics also contribute. This study involved 30 inpatients at St. Madyang Hospital, Palopo, using a five-point Likert-scale questionnaire. The objective was to analyze the factors influencing hospital physical and non-physical development in increasing revenue